2014
DOI: 10.1002/chem.201404350
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐Shaped Silafluorene Derivatives as Efficient Solid‐State UV‐Fluorophores: Synthesis, Characterization, and Photoluminescent Properties

Abstract: Four ring-shaped silafluorene-containing compounds (1-4) were synthesized and characterized as potentially promising monomers for fluorescent polymers. Their optical properties in solution and solid state (thin film and powder) were studied. These compounds have low quantum yields in solution (Φ(fl)=0.13-0.15) with fluorescence maxima at about 355 nm, but high quantum yields in the solid state (powder, Φ(fl)=0.35-0.54) with fluorescence maxima at about 377 and 488 nm. Influence of the substituents and the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…All the chromophores displayed fluorescence quantum yields of φ = ca. 0.1 in n -hexane, consistent with values previously reported for 9 H -9-silafluorenes [20,21,22].…”
Section: Resultssupporting
confidence: 91%
“…All the chromophores displayed fluorescence quantum yields of φ = ca. 0.1 in n -hexane, consistent with values previously reported for 9 H -9-silafluorenes [20,21,22].…”
Section: Resultssupporting
confidence: 91%
“…Although most bond lengths and bond angles of the silole unit in 1-3 are very similar to those found in other silole-containing counterparts (ESI, † Table S2), the C-Si silole -C bond angles (93.801-94.771) are all larger than those observed in the silafluorene-containing cyclosiloxanes (92.61-93.431). 30 We attribute the widening of the C-Si silole -C bond angle to the increased steric clash of the phenyl substituents on the silole group. In general, the cyclosiloxane rings of 1-3 are more nearly planar than those of the silafluorene-containing compounds.…”
mentioning
confidence: 89%
“…Recently, we discovered that silafluorene-containing ringshaped siloxanes a and b (Scheme 1), accessible through a simple co-hydrolysis reaction of 9,9-dichloro-9-silafluorene and the corresponding dichlorosilane derivatives under ambient conditions, display superior solid-state fluorescence properties. 30 Our preliminary analysis revealed that their fluorescence is primarily influenced by the unique way the molecules are packed in the unit cell as well as the electronic properties of the fluorophore moieties. We were thus interested in extending our studies of ring-shaped silole-containing molecules by synthesizing a new class of blue light emitting compounds incorporating tetraphenylsilole as a fluorogenic unit.…”
mentioning
confidence: 92%
“…47 Previously, they reported a series of four ring-shaped siloxane derivatives containing silafluorene units that showed his quantum efficiency in the solid state (Φ f = 0.35-0.54). 48 Pusztai and coworkers synthesized two highly fluorescent blue-emitting bis(diquinaldinatoalumino)-9-silafluorenes that exhibited high quantum efficiency in solution and in the solid-state. 49 All of the new silafluorenes were observed to have strong blue emission both in solution and the solid state, whose physical properties vary upon the alkynyl(aryl) linkages employed.…”
Section: X-ray Crystal Structuresmentioning
confidence: 99%